Pengaruh konsentrasi katalisator dan rasio bahan terhadap kualitas biodiesel dari minyak kelapa - Erna Astuti (Jurnal Rekayasa Proses, 2008)
The demand for energy in Indonesia has increased very fast in the recent years in the midst of fossil oil depletion. A lot of effort has been carried out to find alternative energies. One of the promising alternative energies is biodiesel. Indonesia, as the largest producer of vegetable oil in the world, has an opportunity to play a significant role as a biodiesel producer. Among various vegetable oils, coconut oil is a potential raw material in biodiesel production. The process was carried out in a three-neck round bottom flask equipped with motor stirrer and thermometer. The trans-esterification reaction was conducted by mixing heated coconut oil with a mixture of ethanol and KOH catalyst for two hours. The process variables studied in the present work were catalyst concentration and coconut oil – ethanol ratio. At the optimal condition when the KOH concentration in a range of 0.75-0.90% w/v and a coconut oil – ethanol ratio of 3:1 -5:1, the process produce biodiesel that meets the standard.